Petrogenesis, tectonomagmatic setting and mineralization potential of Dehsalm granitoids, Lut block, Eastern Iran - Arjmandzadeh, R. (2014)
The Dehsalm porphyritic granitoids belong to the Lut Block volcanic-plutonic belt in East - Central Iran. The intrusive rocks range in composition from gabbro - diorite to granite and can be classified as high-K calc alkaline to shoshonitic volcanic arc granites. Elevated contents of Mo, Cu, Au, Pb, Zn occur in silica veins within Bt - Px - Quartz monzonite and Hbl - monzonite. The trend of major oxides on Harker diagrams point to the crystal fractionation of Ca - plagioclase and mafic minerals. Primitive mantle - normalized trace element spiderdiagram displays strong enrichments in LILE such as Rb, Sr, Ba, Zr,Cs and depletions in some high field strength elements (e.g.: Nb, P and Y). Chondrite - normalized plots display significant LREE enrichments (LaN/YbN from 22 to 31) and the lack of Eu anomaly. On the basis of Sr/Y and La/Yb ratios, Dehsalm intrusives cover characteristic features of adakites. (87Sr/86Sr)i and εNdi isotope ratios range from 0.70469 to 0.70505 and from +1.5 to +2.5, respectively, and show that the parental magmas derived from the mantle sources contaminated slightly by crustal materials. The Dehsalm intrusives are classified as magnetite series granitoids and have high mineralization potential for Cu-Mo-Au porphyry type deposits. Two-sided asymmetric subduction explains all the tectonic and magmatic occurrences and the mineralization of porphyry type deposits within the Lut Block during the Tertiary.